2013
DOI: 10.1016/j.vetimm.2012.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a small intestinal segment perfusion model for heat-stable enterotoxin A induced secretion in pigs

Abstract: Enterotoxigenic Escherichia coli (ETEC) are a major cause of dehydrating diarrhoea in children and weaned piglets living under subhygienic conditions. After colonization of the small intestine, ETEC produce heat-labile (LT) and/or heat-stable (ST) enterotoxins. Individual human ETEC strains generally produce only one type of enterotoxin, and in symptomatic patients from developing countries the heat-stable enterotoxin A (STa) producing strains seem by far the most prevalent. STa binds to and activates guanylyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…For instance, when Greenberg et al (42) examined adults with travelers' diarrhea, they demonstrated that fecal lactoferrin and the inflammatory cytokines interleukin-8 (IL-8), IL-1␤, and IL-1ra were elevated in individuals with ETEC travelers' diarrhea. Loos et al (43) examined the role of ST toxins in the induction of early immune responses in piglets after infection with ETEC and demonstrated that the physiological response to ETEC is also accompanied by a marked change in mucosal expression of innate immunity genes. Additionally, LT has been shown to induce the production of cytokines and chemokines from intestinal cells both in vivo and in vitro (35).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, when Greenberg et al (42) examined adults with travelers' diarrhea, they demonstrated that fecal lactoferrin and the inflammatory cytokines interleukin-8 (IL-8), IL-1␤, and IL-1ra were elevated in individuals with ETEC travelers' diarrhea. Loos et al (43) examined the role of ST toxins in the induction of early immune responses in piglets after infection with ETEC and demonstrated that the physiological response to ETEC is also accompanied by a marked change in mucosal expression of innate immunity genes. Additionally, LT has been shown to induce the production of cytokines and chemokines from intestinal cells both in vivo and in vitro (35).…”
Section: Resultsmentioning
confidence: 99%
“…McLamb et al ( 24 ) previously reported that pigs challenged with ETEC have the immune response activated. According to Loos et al ( 46 ), the secretion of IL-6 in the lumen of the small intestine is stimulated by STa produced by E. coli F18 + . In this study, the ETEC challenge increased the concentration of IL-6 as previous reported ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Loos et al ( 46 ), the secretion of IL-6 in the lumen of the small intestine is stimulated by STa produced by E. coli F18 + . In this study, the ETEC challenge increased the concentration of IL-6 as previous reported ( 46 , 47 ). High levels of IL-6 reduce the secretion of growth hormone ( 48 ) and damage the intestinal epithelium ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, using the small intestinal segment perfusion (SISP) technique, STb was shown to play a dominant role during the early secretory response as compared to the contribution of STa and LT [20]. In younger piglets (two weeks old), LT was reported to be a more important virulence factor as compared to STb [20,48,49].…”
Section: Heat-stable Enterotoxins Of Etec From Human and Animal Ormentioning
confidence: 99%